2016
DOI: 10.4103/0975-7406.164293
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory approach for diagnosis of toluene-based inhalant abuse in a clinical setting

Abstract: The steady increase of inhalant abuse is a great challenge for analytical toxicologists. This review describes an overview of inhalant abuse including the extent of the problem, types of products abused, modes of administration, pharmacology and effects of inhalants, the role of laboratory, interpretation of laboratory results and clinical considerations. Regular laboratory screening for inhalant abuse as well as other substance abuse and health risk behaviors must be a part of standard clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…It is largely used all over the world as volatile organic compounds and produced in large quantities to be used in different activities of industrial and commercial applications including paints, varnishes, inks, adhesives, plastics ( 1 , 2 ). Toluene is usually an abused organic solvent and is highly potential for different kinds of abuse ( 3 ). Exposure to toluene may cause damages to variety organs including liver, kidney, lung, heart and nervous system ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is largely used all over the world as volatile organic compounds and produced in large quantities to be used in different activities of industrial and commercial applications including paints, varnishes, inks, adhesives, plastics ( 1 , 2 ). Toluene is usually an abused organic solvent and is highly potential for different kinds of abuse ( 3 ). Exposure to toluene may cause damages to variety organs including liver, kidney, lung, heart and nervous system ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation abuse can harm the body, causing users to feel dizzy, unconscious, and can cause liver, heart, and brain disorders (Edelfield & Moosa, 2011;Glei et al, 2020;Hassan et al, 2017;Jain & Verma, 2016;Knopf, 2021;Real et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Data on the consequences of PVAc and white glue ingestion are rarely found in the literature and most of the available information is associated with bowel obstruction in men (Tanimu et al, 2019) and in some animal species, such as dogs (Lubich et al, 2004). In humans, PVAc poisoning is mostly described in glue sniffing; however, in these cases, damage is caused by inhaling glue additives, such as toluene and other solvents; not described to be present in the ingested white glue (Jain & Verma, 2016). Research, Society and Development, v. 11, n. 12, e144111234047, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i12.34047 6 Experimental studies on PVAc ingestion toxicity were reported in a review by Nair (1992).…”
Section: Discussionmentioning
confidence: 99%